A Study of Spasticity and Functional Outcomes after Phenol Intramuscular Motor Point Block in Neuropathic Patients: The Improvement of Spasticity and Functional Outcome of Phenol Intramuscular Motor Point Block in Patients with Spasticity - A, Kaewma (ASEAN Journal of Rehabilitation Medicine, 2019)
ABSTRACT Objectives: This study was to investigate spasticity and functional outcomes of patient with spasticity after an intramuscular motor point block with phenol. Setting: Rehabilitation Medicine Clinic, Nakornping Hospital. Study design: Retrospective and analytic study. Subjects: Neuropathic patients with spasticity who underwent an intramuscular motor point block with 5% phenol for treatment of spasticity from December 2016 to September 2018. Methods: The modified Ashworth Scale (MAS) for severity of spasticity and the Barthel Index (BI) with maximum score 100 for functional outcomes before and after the intramuscular motor point block was extracted from patients’ medical records and analyzed by using paired t-test and generalized estimating equation (GEE). Complications after phenol block and patients’ opinions were also recorded and reviewed. Results: There were 22 patients. Sixteen were diagnosed with stroke or brain lesion, 3 with spinal cord injury/lesion, and 3 with cerebral palsy. The total number of limbs treated was 71. When counting only the first time of phenol block (n=20), the MAS decreased (mean difference -1.5; 95%CI -1.8, -1.2; p=0.000) and the mean BI increased (mean difference 7.8; 3.1, 12.4; p=0.0024). When counting all treated limbs (n=71), the MAS decreased (GEE coefficient -1.4; 95%CI 1.6, -1.2; p=0.000) and the BI score increased (GEE coefficient 3.5; 95%CI 1.6, 5.5; p=0.000). Complications such as pain, limb swelling, and numbness were reported in 23.9% of the injected limbs. However, all symptoms resolved within a week after treatments. Conclusion: An intramuscular motor point block with 5% Phenol could decrease spasticity and improve functional outcomes in neuropathic patients with spasticity.